The officer's daughter : a memoir of family and forgiveness - Johnson, Elle (Harper, an imprint of HarperCollinsPublishers, 2022)
The author describes the life-altering tragedy she experienced as a teen, when her cousin was murdered in a robbery gone wrong and explains why she needed to meet one of the killers thirty years later at his parole hearing.